Semantics and Pragmatics of Palindromes in Language and Internet Communication - I. N. Ponomarenko; N. A. Segal; I. V. Uvarova (Научный диалог, 2021)
The semantic and pragmatic features of palindromes are considered as an important component of the Russian linguistic picture of the world. The question of establishing the scope and boundaries of the concept of “palindrome” is raised, the specificity of the analysis and interpretation of palindromes in modern linguistic science is characterized, the author’s schemes and classifications of palindromes are proposed based on their structure and semantics. Particular attention is paid to palindromes as an example of linguistic creativity, present both in a literary text and in virtual communication. A review of linguistic research on polyndromia is made. The novelty of the research is seen in the fact that for the first time a comprehensive linguistic analysis of palindromes is carried out as an element of Internet communication, highlighting the most valuable topics and ideas that underlie the modeling of palindromes. It is proved that when palindromes are implemented in the current Internet space, their specificity changes: in contexts, there is a shift in emphasis from aesthetics (form) to pragmatics (content) of palindromes, which fully corresponds to the idea of an anthropocentric paradigm and a semantic-cognitive approach in the study of language.